Herpetic infections in children with acquired immunodeficiency syndrome. - El Hachem, M.; Zicari, L.; Laraia, P.; Heuduck, P.; Boldrini, R.; Castelli Gattinara, G. (European Journal of Pediatric Dermatology, 1999)
Children with acquired immunodeficiency syndrome due to HIV-1 infection are more frequently affected by cutaneous virus infections, especially due to herpes simplex and varicella-zoster virus. Due to the severe compromission of the cell-mediated immunity, these infections are characterized by atypical clinical features and clinical course. Therefore, the clinical diagnosis is often difficult and must be confirmed by the relevant pathological findings. The basic immune depression and the frequent involvement of other organs, besides the skin, require a multidisciplinary diagnostic and therapeutical approach. In fact, the virus infection requires the specific treatment with antiretrovirus drugs, besides acyclovir.